AB1201 MANAGEMENT OF COMORBIDITY IN INFLAMMATORY ARTHRITIS: GECOAI PROJECT. (June 2019) - Castañeda, Santos; Carlos. González, M; Carmen Castro Villegas, María del; García-Díaz, Silvia; Hermosa, Juan Carlos; Lajas, Cristina; León, Leticia; Obaya, Juan Carlos; Rodero, María; Suarez, Carmen; Villaverde, Virginia; Torre-Alonso, Juan Carlos
Abstract : Background: The impact of comorbidity on the diagnosis, prognosis, and treatment of rheumatic diseases could be very high. However, several studies have depicted a sub-optimal assessment of comorbidity in these diseases. Objectives: To generate common, simple and practical support materials (checklists, questionnaires and other complementary materials) for rheumatologists, health professionals and patients, in order to: 1) Assess comorbidity; 2) Identify and implement preventive procedures; 3) Define referral criteria to other health professionals, in patients with rheumatoid arthritis (RA), axial spondylitis (axSpA), and psoriatic arthritis (PsA). Methods: This project was promoted by CONARTRITIS (Association of patients with arthritis), OPENREUMA (Multidisciplinary association of professionals dealing with patients with rheumatic diseases) and SORCOM (Rheumatology Society of the Madrid Region). A multidisciplinary team specialized in comorbidity in inflammatory arthritis was established (6 rheumatologists, 2 primary care physicians, 2 nurses, 1 internist, 1 psychologist). A qualitative study was performed following these phases: 1) Review of the GECOAR 1, GECOAX 2 and GECOAP 3 projects, that were focus on the evaluation of comorbidity in RA, axSpA and PsA, as well as an exhaustive bibliographic search in Medline; 2) Generation of preliminary checklists (different versions and formats) to be used by health professionals and patients for the identification, management and prevention of comorbidity; 3) Patient focus group in which the preliminary patients checklist was evaluated and discussed; 4) Nominal group meeting in which the selected health professionals analyzed all the checklists and modified them taking into account the opinion of the patients; 5) External evaluation of the modified checklists by patients, health professionals and rheumatologists, all of them outside the project; 6) Generation of the final checklists based on everything collected in the previous phases. Results: Three checklists for clinical practice were designed, two for health professionals (one to identify comorbidity, another on prevention/health promotion), one for patients. The comorbidity checklist includes, for example, the evaluation of cardiovascular risk factors, depression and anxiety, allergies or infections. The prevention checklist includes life style issues (smoking, diet, exercise), social life, sexuality, sleep, or oral hygiene. The checklists also specify the evaluation method (questions, specific questionnaire, etc.). Conclusion: The use of specific checklists for the identification, management and prevention of comorbidity inpatients with RA, axSpA and PsA might contribute positively in their prognosis. References: [1] Loza E, et al. Rheumatol Int. 2015 Mar;35(3):445-58. [2] González C, et al. Reumatol Clin. 2018 Nov - Dec;14(6):346-359. [3] Torre-Alonso JC, et al. Rheumatol Int. 2017 Aug;37(8):1239-1248. Disclosure of Interests: Santos Castañeda Consultant for: Amgen, BMS, Pfizer, Lilly, MSD, Roche, Sanofi, UCB, Carlos M. González: None declared, María del Carmen Castro Villegas Paid instructor for: MSD, Abbvie, Pfizer, Janssen, Lilly, Roche, Silvia García-Díaz: None declared, Juan Carlos Hermosa: None declared, Cristina Lajas: None declared, Leticia León: None declared, Juan Carlos Obaya: None declared, María Rodero: None declared, Carmen Suarez: None declared, Virginia Villaverde: None declared, Juan Carlos Torre-Alonso: None declared